Lifestyle, morbidity and multimorbity in adult Quilombolas - Almeida, Ingred Laíla da Silva; Santos, Saul Ricardo dos; Queiroz, Bruno Morbeck de; Mussi, Ricardo Fraklin de Freitas (ABCS Health Sciences, 2020)
Introduction: The negative lifestyle has been associated with adverse health conditions, predisposing to the increase of morbidity and mortality in various populations. Objective: To evaluate the association of lifestyle with morbidities and multimorbidity in adult quilombolas, residents of slave descendant communities (quilombos). Methods: Cross-sectional study with a representative sample of adult living in quilombos located in a geographical region of Bahia State, in Brazil. Data were obtained by applying a standardized form for sociodemographic characteristics and morbidities. Lifestyle was evaluated using the questionnaire Perfil de Estilo de Vida Individual (PEVI), encompassing the domains: nutrition, physical activity, preventive behavior, social relationships and stress control. Poisson regression was used to estimate prevalence ratios, with statistical significance for p<0.05. Results: Negative PEVI score were identified in 18.5% of the quilombolas. High blood pressure, central obesity and multimorbity affected 53.5%, 56.2% and 50.2% of the population, respectively. Men had more positive PEVI score, however the nutrition domain was more negative. Physical activity and stress control domains from women were more negative. Central obesity was associated to the domain of physical activity. Dyslipidemias and multimorbidity were associated with the domain of preventive behavior. Conclusion: About one fifth of the quilombolas presented negative PEVI and high prevalence of morbidity and multimorbidity. The different associations between PEVI and its domains (physical activity, preventive behavior and stress control) reveal that the adoption of positive health habits infers in the presence of morbidities.